The share of health care spending in the structure of GDP as a criterion for the healthcare system effectiveness - Zyukin, Danil Alekseevich; Bystritskaya, Anna Yurievna; Golovin, Artem Alekseevich; Vlasova, Olga Vladimirovna (Revista de la Universidad del Zulia, 2020)
Effective work of the healthcare system is becoming increasingly important in modern conditions, which actualizes the task of finding tools to increase the effectiveness of its functioning; this should ultimately lead to a decrease in morbidity and an increase in life expectancy. One of the main criteria for social development in modern conditions is the share of health care spending as a percentage of GDP; since this reflects the degree of attention and concern of the state about the health and life of citizens. The research hypothesis states that the share of health care costs does not affect the quality of the health care system, which is expressed in the average life expectancy of the population. To confirm the hypothesis, an analysis was made of the degree of influence of the share of expenditures on health care development on GDP on average life expectancy in the context of countries using a simple pair correlation and correlation between ranks; A cluster analysis of the countries was also carried out on the basis of their grouping according to the level of health spending as a percentage of GDP. It has been established that there is no connection between the share of health expenditures from GDP in countries and average life expectancy in them, which confirms the failure to use this indicator as a criterion for assessing the development of the health system. A cluster analysis of the countries under consideration showed that the effectiveness of the health care system is a complex category, depending not only on the level of state funding, but also on a number of other aspects.